Cartographies of Copyright: Crisis & Propertization - Flanders, Paul (My University, 2017)
Cartographies of Copyright is a cultural history of copyright that maps out various contradictions and tensions that give shape to the crisis of copyright and its relations to US music industries. More specifically, this work charts the radical dissension of copyright in recent history and argues for an understanding of the crisis as an internal transformative process. This formulation shifts the analytic approach from an abstract conceptual-legal perspective to a series of discrete points within a lived history, culture and materiality of copyright thought, audio technologies and neoliberal capitalism. Seen in terms of territorialization, the expansion of copyright via the music industries gives unique insight into the particular ways music and its media formats effect the evolution of copyright culture and law. When framed this way, an investigation into music and copyright leads to recognizing new forms of control, changing modes of administering access and contemporary relations of power. To chart the effects of these transformations I draw upon the tensions and problematics that constitute the Wu-Tang Clan’s 2015 one-of-a-kind release: Once Upon A Time In Shaolin. After accessing contentious foci within traditional copyright paradigms, I argue that classical models lack explanatory power, pose problems for understanding the transformations of copyright throughout history and fail to provide a comprehensive account of the present crisis. Taking inspiration from the reoccupation thesis presented by Hans Blumenberg and recent research in copyright I propose an alternative model rooted at the dialectic crux of property metaphors, audio technologies and formats, and neocapitalist commodity logic––all of which give shape to an internal transformation within copyright law and culture I term propertization. Cartographies of Copyright is not a legal treatise, per se; rather, the work sees law as text set within a larger social milieu liable to change and evolution. Drawing from legal theory, cultural studies and media studies the work engages copyright from the perspectives of critical history, rhetoric, media-materiality and speculative economics. The multidisciplinary approach also stakes out new formations to the problematics faced by music historically and to draw connections between the music industries and the broader social contexts they are situated in. Cartographies argues for a new lexicon to begin imagining alternative models to account for copyright’s transformations––ones better suited to imagining viable alternatives. It calls attention to the urgent need of public discussion concerning the role of copyright in contemporary music and culture and provides modest suggestions for thinking about the future of the copyright regime and the musical properties within it.